PENGUASAAN KETERAMPILAN DASAR MENGAJAR MAHASISWA PRAKTIK PENGALAMAN LAPANGAN FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Nuristiqamah Awaliyahputri Baharuddin; Siti Syamsudduha; Muhammad Shabir Umar (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2020)
Through field study, it was found that some students who did PPL is not mastering the basic skill of teaching maximally. If the PPL students master the basic skill of teaching maximally, they will used as a refference to become the real educator, not only know the theory but also could be successfully apply it as practices. The aim of this research is to map the PPL students mastery of basic teaching. The type of this research was descriptive qualitative with study case as the strategy of the research. This research take place at MA Madani Alauddin Paopao, Gowa regency, Makassar city. Sources of this research are Students, tutor, and documents. Research instruments are observation checklist, students’ guideline, and documentation checklist. As the result, researcher found that PPL students’ teaching skill mastery is fairly good, namely opening skills lessons, skill to provide reinforcement, skills of teaching variations, skills to guide small group discussions, as well as small group and individual teaching skill. Component basic teaching skills that are not good, namely skills advanced questioning, explaining skills, and classroom management skills.